Analisis Kinerja Guru Sertifikasi dan Non Sertifikasi pada SMP Se-Kecamatan Kota Masohi Kabupaten Maluku Tengah - Meirani Nakul; Izaak Hendrik Wenno; Lamberthus Johannes Lokollo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Within the framework of national education reform, teacher certification serves as a strategic instrument to enhance professional competence and pedagogical performance. This research was motivated by the limited empirical evidence explaining the relationship between certification, professional motivation, and teaching quality in Indonesia’s island-based regions. The study aims to examine the influence of teacher certification on professional motivation and its implications for instructional quality among junior high school teachers in Central Maluku Regency. Employing a mixed-methods convergent design, data were collected through a quantitative survey of 60 teachers and in-depth interviews with school principals and education supervisors. The findings indicate a significant positive correlation between certification and professional motivation (r = 0.673; p < 0.01), with a direct effect on teaching quality, particularly in instructional planning and reflective practice. Qualitative insights reveal that certification fosters teacher reflectivity, professional accountability, and peer collaboration grounded in local pela gandong values. Conceptually, this study extends transformational leadership theory into a context-specific framework of teacher professionalism within island education systems